Respuesta :

The simplified expression is [tex]\bold{18x^2 -15x + 2}[/tex].

Step-by-step explanation:

We are given an expression of the form:

[tex](6x-1)(3x-2)[/tex]

We have to expand and simplify the the given expression.

We can use the algebraic identity:

[tex](a+b)(c+d) = ab + ad + bc + bd[/tex]

Using the above identity, we get:

[tex](6x-1)(3x-2)\\= (6x)(3x) + (6x)(-2) + (-1)(3x) + (-1)(-2)\\= 18x^2 - 12x -3x +2\\= 18x^2 -15x + 2[/tex]

The simplified expression is [tex]\bold{18x^2 -15x + 2}[/tex].

ACCESS MORE